Alcohol consumption as a risk factor for tuberculosis: meta-analyses and burden of disease. Issue 1 (13th July 2017) - Imtiaz, Sameer; Shield, Kevin D.; Roerecke, Michael; Samokhvalov, Andriy V.; Lönnroth, Knut; Rehm, Jürgen
Meta-analyses of alcohol use, alcohol dosage and alcohol-related problems as risk factors for tuberculosis incidence were undertaken. The global alcohol-attributable tuberculosis burden of disease was also re-estimated. Systematic searches were conducted, reference lists were reviewed and expert consultations were held to identify studies. Cohort and case-control studies were included if there were no temporal violations of exposure and outcome. Risk relations (RRs) were pooled by using categorical and dose-response meta-analyses. The alcohol-attributable tuberculosis burden of disease was estimated by using alcohol-attributable fractions. 36 of 1108 studies were included. RRs for alcohol use and alcohol-related problems were 1.35 (95% CI 1.09–1.68; I 2 : 83%) and 3.33 (95% CI 2.14–5.19; 87%), respectively. Concerning alcohol dosage, tuberculosis risk rose as ethanol intake increased, with evidence of a threshold effect. Alcohol consumption caused 22.02 incident cases (95% CI 19.70–40.77) and 2.35 deaths (95% CI 2.05–4.79) per 100 000 people from tuberculosis in 2014. Alcohol-attributable tuberculosis incidence increased between 2000 and 2014 in most high tuberculosis burden countries, whereas mortality decreased. Alcohol consumption was associated with an increased risk of tuberculosis in all meta-analyses. It was consequently a major contributor to the tuberculosis burden of disease. Alcohol use, alcohol dosage and alcohol-related problems are associated with an increased risk of tuberculosis http://ow.ly/CheO30aPqJg